Role of Adiponectin in Central Nervous System Disorders. (29th July 2018) - Bloemer, Jenna; Pinky, Priyanka D.; Govindarajulu, Manoj; Hong, Hao; Judd, Robert; Amin, Rajesh H.; Moore, Timothy; Dhanasekaran, Muralikrishnan; Reed, Miranda N.; Suppiramaniam, Vishnu
Abstract : Adiponectin, the most abundant plasma adipokine, plays an important role in the regulation of glucose and lipid metabolism. Adiponectin also possesses insulin-sensitizing, anti-inflammatory, angiogenic, and vasodilatory properties which may influence central nervous system (CNS) disorders. Although initially not thought to cross the blood-brain barrier, adiponectin enters the brain through peripheral circulation. In the brain, adiponectin signaling through its receptors, AdipoR1 and AdipoR2, directly influences important brain functions such as energy homeostasis, hippocampal neurogenesis, and synaptic plasticity. Overall, based on its central and peripheral actions, recent evidence indicates that adiponectin has neuroprotective, antiatherogenic, and antidepressant effects. However, these findings are not without controversy as human observational studies report differing correlations between plasma adiponectin levels and incidence of CNS disorders. Despite these controversies, adiponectin is gaining attention as a potential therapeutic target for diverse CNS disorders, such as stroke, Alzheimer's disease, anxiety, and depression. Evidence regarding the emerging role for adiponectin in these disorders is discussed in the current review.